Evolusi Pemikiran Ekonomi Islam: dari Islamic Golden Age hingga Tantangan Ekonomi Modern - Sulistya Ningsih; Tarmizi Silalahi; Faris Haikal Hasibuan; Ahmad Wahyudi Zein (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Islamic economic thought experienced significant development during the Islamic Golden Age, with Muslim scholars making major contributions to global economic knowledge. During this period, thinkers such as Al-Farabi, Ibn Khaldun, and Al-Ghazali introduced concepts focused on justice, social welfare, and a balance between material and spiritual needs. Through the translation of scholarly works, many Islamic economic concepts were transmitted to Europe, which was experiencing intellectual stagnation during the Dark Ages. This influence helped revive interest in economic thought in the West, particularly during the Renaissance. However, following the Islamic Golden Age, a substantial gap emerged in economic thought development between the Islamic world and the West. As the West progressed through the Industrial Revolution and the rise of capitalism, Islamic economic thought faced a period of stagnation. This article examines the historical development of Islamic economic thought, the impact of knowledge transmission from the Islamic world to the West, and the relevance of Islamic economics in addressing modern economic challenges such as social inequality, financial crises, and the need for a more ethical and sustainable economic system.